The prevalence and distribution of human papillomavirus in 4267 Turkish women with or without cervical lesions: A hospital‐based study. Issue 10 (23rd June 2022) - Altay‐Kocak, Aylin; Kazanci, Ferah; Dogu‐Tok, Canan; Onan, Anil; Erdem, Ozlem; Ozkan, Secil; Bozdayi, Gulendam
Abstract: In the present study, it was aimed to screen the genotypes of human papillomavirus (HPV) retrospectively in women with gynecological symptoms who were admitted to a tertiary care university hospital in Ankara, Turkey. A total of 4267 cervical swab samples of women aged 18–79 years were sent to Medical Virology Laboratory from January 2017 to November 2020. Nucleic acid extraction and amplification of samples were done by an automated system. The test can detect 14 high‐risk HPV (HR‐HPV) types in a single analysis that performs a real‐time polymerase chain reaction, by providing individual results on the highest‐risk genotypes HPV 16 and HPV 18 and pooled results on other high‐risk genotypes (OHR‐HPV) (31, 33, 35, 39, 45, 51, 52, 56, 58, 59, 66, 68). HPV DNA positivity was detected in 14.2% (605/4267) of the samples. HPV type 16 and type 18 were detected in 2.4% and 0.7% of the samples, respectively. OHR‐HPV types were found in 8.8% of the samples. Of the 1.9% and 0.4% samples had mixed types with type 16+ OHR‐HPV and type 18+ OHR‐HPV, respectively. The results of this study presented the rates of HR‐HPV genotypes of a university hospital in Ankara, over a 4‐year period. It was observed that the positivity rate of type 18 is decreasing and some OHR‐HPV types are increasing. HPV vaccination is not in the national immunization program in Turkey yet, however,  HPV vaccines are available and the vaccination rates for women are increasing.